Students’ Habits and Identification of Bacteria on Inanimate Surface of Educational Setting - Udijono, Ari; Subagio, Agus; Adi, Mateus Sakundarno; Widjanarko, Bagoes; Fauzi, Muhammad; Kusariana, Nissa; Sutiningsih, Dwi (Universitas Airlangga, 2024)
Introduction: Diponegoro Clinic reported 29.1% of students seek infectious diseases treatment. Student habits in the classroom were thought to play roles in the presence of bacteria. Surfaces of inanimate objects in the classroom were potential source for bacteria. The research objectives were analyzing student’s habits and identifying bacteria on the surface of inanimate objects in the classroom. Methods: Four types of samples, including the surfaces of tables, chairs, flips of air conditioners, and floors were taken from 13 faculties at Universitas Diponegoro. Plate count agar media were used to isolate bacterial colonies, and PCR analysis was performed for DNA extraction and amplification. DNA Sanger sequencing techniques were used for genetic bacterial identification. The online questionnaire was used to assess student habits in the classroom. Two hundred students responded. Results and Discussion: Acinetobacter baumannii and Staphylococcus aureus were found in classrooms. These bacteria were associated with respiratory tract infections. This study revealed that 86.5% were between the ages of 17-21, 60.81% were from outside Semarang City, and 88.33% lived in Semarang City. About 60.81% of respondents studied in health sciences. Furthermore, it was reported that 66.67% of respondents were sick in the last few weeks, attended class despite being sick (72.52%), and coughed and sneezed in class (40.99%). Conclusion: Bacteria associated with respiratory tract infection were found. Students' habits in the classroom were potentially caused by the presence of these bacteria. The use of antibacterial agents could reduce the presence of bacteria on inanimate object surfaces.